2012
DOI: 10.1111/ijpp.12005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical pharmacy services on stress ulcer prophylaxis prescribing and related cost in patients with renal insufficiency

Abstract: This study showed that implementing institutional guidelines, and active involvement of clinical pharmacists in the nephrology healthcare team, could reduce inappropriate SUP prescribing and related costs for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
2
22
0
1
Order By: Relevance
“…Studies included in this review had investigated the effectiveness of a variety of interventions in different health setups. Although computerised and manual interventions were effective in reducing IP, prompting physicians with eGFR values did not result in significant reduction . Similar to a previous review, clinical outcomes have shown better improvement in pharmacist‐based interventions than in computerised ones .…”
Section: Discussionsupporting
confidence: 73%
“…Studies included in this review had investigated the effectiveness of a variety of interventions in different health setups. Although computerised and manual interventions were effective in reducing IP, prompting physicians with eGFR values did not result in significant reduction . Similar to a previous review, clinical outcomes have shown better improvement in pharmacist‐based interventions than in computerised ones .…”
Section: Discussionsupporting
confidence: 73%
“…Recommendations were made to physicians and nurses at that time. All pharmacist recommendations were verbal and recorded on a specially designed pharmacist intervention form Dosing adjustments were related to a reduced length of ICU stay from 10.7 ± 11.1 days to 7.7 ± 8.3 days ( p = 0.037) in the intervention group, and to cost savings of 3525 USD (13,463 ± 12,045 vs. 9938 ± 8811, p = 0.038) per septic patient receiving CRRT in the ICU Suspected antimicrobial adverse drug events in the intervention group were significantly fewer than in the pre-intervention group (19 events vs. 8 events, p = 0.048) Dosing error events were significantly fewer in the post-intervention phase than in the pre-intervention phase (54 in 73 patients vs. 194 in 71 patients, p < 0.001) Mousavi et al (2013) Iran [ 22 ] Retrospective/Prospective uncontrolled study (12 months) University hospital based nephrology wards To evaluate appropriateness of acid suppression therapy in kidney disease patients and to assess the role of clinical pharmacists to decrease inappropriate SUP prescribing and related costs for these patients Pre-test phase (375 patients) Post-test phase (236 patients) Pre-test phase 51.2 (18.3) Post-test phase 50.2 (18.8) Pre-intervention phase: patient chart review by CP, develop SUP protocol, and provide educational sessions to doctors on SUP Post-intervention phase: Clinical pharmacists accompanied physicians on the ward rounds and advised on starting or stopping SUP Not reported Rani et al (2013) India [ 50 ] Prospective uncontrolled study (3 months) Dialysis unit of a multispecialty university hospital To assess the medication knowledge of CKD patients undergoing HD, to assess the effect of a CP provided continuous patient education in improving medication adherence and to evaluate the association between medication knowledge and medication adherence behaviour in HD patients 85 HD patients 50.52 (13.28) Patient counselling and education (verbally and written). Patient interview to assess medication knowledge using MKAQ.…”
Section: Resultsmentioning
confidence: 99%
“…3,10,12,16,17,21 High prevalence of irrational prescribing in some institutes necessitated clinical pharmacist intervention, which could improve the prescription pattern of SUP administration in certain hospital wards. 22,23 …”
Section: Discussionmentioning
confidence: 99%